PENYAJIAN LAPORAN KEUANGAN, KOMPETENSI APARATUR PEMERINTAH, DAN PENGELOLAAN KEUANGAN DAERAH - Maria Maria; Zulkifli Zulkifli; Riza Wahyudi; Amira Fairuzdita (Department of Accounting, Faculty of Economics and Business, Universitas Tadulako, 2020)
This study aimed to know the influence of financial statement presentation and competency of regional government apparatus in South Sumatera province (Indonesia), both simultaneously and partially toward the financial management accountability. The research method used in this study was explanatory research with 59 respondents at regional financial and asset management agency. The analysis unit of government officials was divided into budgeting department, treasury department, accounting department, and management of regional property department. Data analysis was performed by using multiple regression. The result of study showed that financial statement presentation and competency of regional government apparatus gave 78,7% effect on financial management accountability. Partially, competency of regional government apparatus accessibility on financial management accountability gave bigger contribution compared to financial statement presentation.